Cluster-randomised trial on participatory community-based outdoor physical activity promotion programs in adults aged 65-75 years in Germany: protocol of the OUTDOOR ACTIVE intervention trial - Karin Bammann; Carina Drell; Lena Lotte Lübs; Imke Stalling (BMC, 2018)
Abstract Background Despite its well-known benefits for health and well-being physical activity levels are insufficient and declining with age in Germany. Physical activity promotion programs for older adults are often not successful, one reason is insufficient relevance of intervention measures for the study population. Community-based participatory research (CBPR) is a possible key strategy for tailoring more meaningful intervention programs to a specific community. However, evidence for the effectiveness of CBPR in the general population is scarce. This study aims to formally evaluate the efficacy of a CBPR approach for developing and implementing an outdoor physical activity program for older adults. Methods/design The OUTDOOR ACTIVE intervention trial is a cluster-randomised intervention study carried out in a random sample of eight subdistricts in the city of Bremen, Germany. The eight subdistricts are grouped into four homogenous pairs with regard to socioeconomic level and land use mix of the subdistrict. Within the pairs, the subdistricts are assigned randomly to the two study arms: participatory development and implementation of a community-based program to promote outdoor physical activity (intervention) versus no intervention (controls). For evaluation, a survey is carried out before (baseline) and after (follow-up) the intervention period. The measurements include 7-day accelerometer measurement, physical fitness test, blood pressure, basic anthropometry, and self-administered questionnaire. Discussion The OUTDOOR ACTIVE intervention trial will provide detailed information on PA intervention for older adults in an urban setting. Through the participatory nature of the study it will provide valuable insights into drivers and barriers to PA in this group, and it will inform policy makers and other stakeholders how to benefit from the results. Trial registration German Clinical Trials Register DRKS00015117 (Date of registration 17-07-2018).